Autologous stem cell transplantation in elderly patients with multiple myeloma: evaluation of its safety and efficacy. Issue 5 (4th May 2017) - Stettler, Jasmin; Novak, Urban; Baerlocher, Gabriela M.; Seipel, Katja; Mansouri Taleghani, Behrouz; Pabst, Thomas
Abstract: Administering high-dose chemotherapy (HDCT) with melphalan to elderly myeloma patients represents a challenge with respect to achieving therapeutic efficacy whilst avoiding significant toxicity. We analyzed safety and efficacy of HDCT in 61 elderly myeloma patients older than 65 years, including 12 patients ≥70 years, and compared them with 237 MM patients below 65 years treated in the same period. We observed no differences in the time until neutrophil recovery, infection rate, and treatment related mortality until 100 days after ASCT. Furthermore, higher age was not associated with inferior progression-free and overall survival at 1 and 2 years after ASCT. However, MM patients older than 70 years had a longer duration of hospitalization (26 vs. 20 days; p = .0001) and a longer time until platelet recovery >20G/L (20 vs. 13 days; p = .0007). Our data suggest that HDCT with ASCT is feasible, safe and effective in MM patients older than 65 years.